Institutional Quality and Trade Flow: Empirical Evidence from Malaysia and Other OIC Member Countries in Africa. Issue 2 (July 2021) - Yusuf, Hammed Agboola; Afolabi, Luqman Olanrewaju; Shittu, Waliu Olawale; Gold, Kafilah Lola; Muhammad, Murtala
This article examines the impact of institutional quality on bilateral trade flow between Malaysia and selected 25 African Organisation of Islamic Cooperation (OIC) member countries. Four institutional qualities were selected from World Governance Indicators with other trade predictors from the period from 1985 to 2016. Using gravity model of trade and Poisson pseudo-maximum likelihood estimation method (PPML) technique, the results confirm that government effectiveness, regulatory quality and political stability have an adverse effect on bilateral trade flow among the OIC countries in Africa. On the other hand, these institutional quality variables were considered as a strength for Malaysian economic growth. Therefore, better institutional quality reforms are needed among OIC member countries in Africa in order to accelerate trade, economic growth and development in their region.